ANALISIS SPASIAL TEKANAN PENDUDUK TERHADAP LAHAN PERTANIAN DI SUB DAS KEDUANG, KABUPATEN WONOGIRI, JAWA TENGAH - Agus Wuryanta; Pranatasari Dyah Susanti (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2015)
Population pressure on agricultural land is one of  the important parameters to determine the level of  watershed environment quality. High population pressure on agricultural land in a watershed can lead to land degradation and watershed ecosystems damage. The purpose of  research is to calculate and determine the level of  population pressure on agricultural land in the sub watershed and in each district in the sub watershed by using Geographic Information System (GIS). Population pressure on agricultural land is calculated by using Soemarwoto's formula (1985). The classification of  population pressure on agricultural land is based on the Decree of  the  Directorate General of  Land Rehabilitation and Social Forestry (RLPS,) Ministry of  Forestry of  Indonesia No. P.04/VSET/2009. The research was conducted in Keduang sub-watershed which is part of  water chatchment area of  Gajah Mungkur Reservoir in Wonogiri District, Central Java. The results showed that population pressure on agricultural land in Keduang Sub-watershed is categorized as “bad” with the value of  28.978,16. Girimarto, Jatipurno, Jatiroto, Jatisrono and Sidoharjo districts are categorized as “medium”, while Jatiyoso, Kismantoro, Ngadirojo, Nguntoronadi, Purwantoro, Slogohimo and Tirtomoyo districts are categorized as “bad” with the value more than 2.